Characterization of Antibiofilm Molecules from Bovine Coagulase-Negative Staphylococci - Coralie Goetz; Ibtissem Doghri; Sneha Das; Audrey Corbeil; Pauline Bouveret; Francis Beaudry; David Lalaouna; Eric Massé; Mario Jacques; François Malouin (PLoS ONE, 2026)
Bacterial biofilms are structured communities of bacterial cells enclosed in a self-produced polymeric matrix, which can adhere to biotic or abiotic surfaces. This mode of existence permits these bacteria to endure in adverse conditions, including the presence of antibiotics Bacteria within biofilms are responsible for numerous infections in humans and animals, including bovine mastitis. It is therefore important to develop new therapeutic strategies to control and treat biofilm-associated infections. The results obtained by our group during the study of mixed bacterial biofilm communities showed that four isolates of coagulase-negative staphylococci (CNS; two Staphylococcus chromogenes and two Staphylococcus simulans ) that produce only a small amount of biofilm can significantly reduce biofilm formation in approximatively 80% of pathogenic staphylococci associated with bovine mastitis. Furthermore, supernatants of S. chromogenes reduced secondary intramammary colonization by S. aureus in a murine model of mastitis. However, information regarding the mechanism and the effector molecule(s) involved is lacking. The objective of this study was therefore to investigate and characterize the antibiofilm molecule(s) produced by these four CNS isolates. In this context, we prepared culture supernatants from two isolates of S. chromogenes (C and E) and two isolates of S. simulans (F and H) to evaluate their effect on biofilm production of pathogenic bacterial species involved in bovine mastitis. Using a standard biofilm microtiter plate assay, we demonstrated that the four CNS supernatants not only have a significant impact on biofilms of pathogenic staphylococci (68% of tested isolates) but also on those of other important mastitis pathogens such as Streptococcus spp., Trueperella pyogenes , Klebsiella spp. and Escherichia coli (61.3% of tested isolates) . The isolation and characterization of the antibiofilm molecule(s) contained in the supernatants were then conducted using a filtration process with membranes of different porosities, as well as through physicochemical and enzymatic treatments. We were then able to confirm that antibiofilm activity against staphylococci was present in the < 3kDa fractions of CNS culture supernatants and that this activity was heat-stable and protease-resistant, but sensitive to RNase A, suggesting that the antibiofilm activity might be due, at least in part, to an RNA molecule. Preliminary results showed that the antibiofilm activity was maintained with RNA extracts from fractioned supernatants (<3kDa). In conclusion, these results confirmed that some CNS have an antibiofilm activity, which represents a promising new avenue in the fight against biofilm-associated infections, particularly bovine mastitis.